2021
DOI: 10.3389/fmolb.2021.625391
|View full text |Cite
|
Sign up to set email alerts
|

Appraisals of the Bangladeshi Medicinal Plant Calotropis gigantea Used by Folk Medicine Practitioners in the Management of COVID-19: A Biochemical and Computational Approach

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first recognized in Wuhan in late 2019 and, since then, had spread globally, eventually culminating in the ongoing pandemic. As there is a lack of targeted therapeutics, there is certain opportunity for the scientific community to develop new drugs or vaccines against COVID-19 and so many synthetic bioactive compounds are undergoing clinical trials. In most of the countries, due to the broad therapeutic spectrum and minimal side effects, medicina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…These compounds appeared to bind to the substrate binding site of Mpro, specifically His41–Cys145 catalytic dyad, except for chelidimerine and adlumidine. SARS-CoV-2 Mpro is a cysteine protease (CP) with a catalytic dyad in the active site Cys145/His41, similar to other CPs [ 46 , 47 ]. On the other hand, several researchers have previously reported that amino acid residues on RBD of SARS-CoV-2 that bind to hACE2 are Lys417, Tyr449, Gln493, Gly496, Gln498, Thr500, and Gly502 [ 48 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…These compounds appeared to bind to the substrate binding site of Mpro, specifically His41–Cys145 catalytic dyad, except for chelidimerine and adlumidine. SARS-CoV-2 Mpro is a cysteine protease (CP) with a catalytic dyad in the active site Cys145/His41, similar to other CPs [ 46 , 47 ]. On the other hand, several researchers have previously reported that amino acid residues on RBD of SARS-CoV-2 that bind to hACE2 are Lys417, Tyr449, Gln493, Gly496, Gln498, Thr500, and Gly502 [ 48 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Nepal, there were also 60 medicinal plants used ( Khadka et al, 2021 ) and 23 plants in Morroco ( El Alami et al, 2020 ) for potential COVID-19 therapy and Zingiber officinale is one of the common species used. In Bangladesh, phytochemicals extracted from Calotropis gigantea exhibited positive inhibitory effects against the COVID-19 virus ( Dutta et al, 2021 ), as well as the alkaloids and terpenoids isolated from plants of African origin ( Gyebi et al, 2021 ). Curcumin from C. longa also showed promising effects against the virus ( Adhikari et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Computer-aided drug design may represent a potential method for identifying lead compounds to treat SARS-CoV-2, which can result in both rapid and accurate results. A plethora of studies that have applied computational biology techniques have successfully predicted novel lead compounds for combating SARS-CoV-2 in addition to designing in silico epitope-based vaccines against SARS-CoV-2 [ 2 , 5 , 30 , 52 , 53 ]. However, these types of studies continue to require further wet-lab verification to be developed into effective therapeutic strategies for COVID-19.…”
Section: Discussionmentioning
confidence: 99%